2020
DOI: 10.3390/foods9060802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Timing and Temperature of Malolactic Fermentation on the Aroma Composition and Mouthfeel Properties of Chardonnay Wine

Abstract: Malolactic fermentation (MLF) is an important process in wine production due to the resulting reduction in acidity. MLF is typically induced by the addition of Oenococcus oeni after the completion of alcoholic fermentation (AF), but can occur concurrent with AF by co-inoculation of O. oeni with Saccharomyces cerevisiae. This study investigated the effect of MLF inoculation timing and temperature (15 °C and 21 °C) and the presence of the non-Saccharomyces yeast Torulaspora delbrueckii on Chardonnay wine aroma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
(40 reference statements)
0
9
0
2
Order By: Relevance
“…Therefore, the warmer the climate or the later the harvest is planned, the more sugar will develop in the bunches and somehow balance the acidity of the product. Thus, in regions with a relatively cold climate, dry wine can be achieved by the conversion of an excessive amount of malic acid into lactic acid by malolactic fermentation initiated by lactic acid bacteria [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the warmer the climate or the later the harvest is planned, the more sugar will develop in the bunches and somehow balance the acidity of the product. Thus, in regions with a relatively cold climate, dry wine can be achieved by the conversion of an excessive amount of malic acid into lactic acid by malolactic fermentation initiated by lactic acid bacteria [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chardonnay is a white grape variety known as a neutral aromatic variety that produces wines without a peculiar set of aroma compounds [ 15 ]. It easily adjusts to many different terroirs in almost every wine-growing region [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli have shown that they successfully withstand winemaking conditions and possess many advantageous properties that make them appropriate for MLF management [31,32]. Besides their malolactic activity, these LAB detain complex secondary metabolisms that can positively influence a wine's final aroma and flavour, including synthesis or catalysis of citrates, amino acids, polysaccharides, aldehydes, and esters [33,34]. In particular, Lactiplantibacillus plantarum strains can promote MLF under high pH conditions, avoiding acetic acid synthesis due to their facultative heterofermentative features, and modifying wine aromas because of a more composite enzymatic profile when compared to O. oeni [31,32].…”
Section: Lab In Oenology: Introductory Aspects and Biodiversitymentioning
confidence: 99%